The stages of the play’s development from the ancient era to the Umayyad era - Bazuhair, Narjees Abdulghaffar Saeed (Journal of Humanities & Social Sciences, 2023)
The play is one of the ancient literary type that have passed through different historical stages since its inception in ancient times in the Sumerian and Babylonian civilizations in the Euphrates land in Iraq, the Pharaonic in the Nile Valley in Egypt, the Greeks in Greece and the Romans, the pre-Islamic era, and the early Islam. These different stages in which this beautiful literary art developed, and it made great strides towards progress until it reached the end of the Umayyad era, and the beginning of the Abbasid era when the Abbasid state was established in the year 132 AH. It was found through the study that the play had gone through several stages, and it began with primitive dance in religious ceremonies, in temples, at weddings, when sowing, harvesting, etc. The question is in which of these ancient era appeared the play first?